An SMS-Guided Basal Insulin Titration in People with Type 2 Diabetes New on Insulin - Snel, Tim; Reinhardt, Sven; Koenig, Helena; Pleus, Stefan; Freckmann, Guido (Diabetes therapy, 2024)
Introduction The shortage of general practitioners (GPs) and the increasing prevalence of type 2 diabetes create significant pressure on primary healthcare services. To enable that medical services are available to all that need it, innovative solutions are needed. One of those, a Short Message Service (SMS)-supported basal insulin titration service is investigated in this study. The primary objective was to determine the percentage of subjects who achieved stable fasting blood glucose (FBG) within their individual target range with this service after week 16. Methods This single-arm, 16-week study aimed to enroll 111 adults diagnosed with type 2 diabetes that needed insulin. The study subjects measured their FBG 4 consecutive days to establish a baseline, then received SMS prompts for daily FBG measurements and evening insulin injections until their FBG stabilized within the target range. Adjusting the insulin based on the FBG. Once stabilization was achieved, subjects continued with their optimal insulin dose for the remainder of the study. Sixteen weeks after the baseline, subjects measured FBG for 4 days before visit 4, where these values were read by the healthcare provider. Results Out of the planned 111 subjects, only 30 were enrolled, with one withdrawal prior to service activation. Challenges in subject recruitment were attributed to the COVID-19 outbreak, limited eligibility, competing studies, and new medications delaying insulin initiation. Subjects were on average 59.97 years old, had an HbA1c of 9.29% a FBG of 205.64 mg/dl, and had diabetes for 10 years. Among the 29 subjects who started the service, 72% achieved successful titration at visit 4, with a median time of 49 days. Notable improvements were observed in HbA1c levels (decreased by 1.58%) and FBG levels (decreased by 64 mg/dl) over the 16-week study period. No adverse events or device-related issues were reported. Conclusions Despite recruitment challenges, guided basal insulin titration holds promise for insulin therapy initiation in individuals. The findings emphasize the potential of tele-medical approaches, specifically through remote messaging, in managing diabetes and improving therapy adherence.